Temperature mediated albedo decline portends acceleration of North American glacier mass loss - S. N. Williamson; S. J. Marshall; B. Menounos (Communications Earth & Environment)
Abstract North American glaciers experienced accelerated mass loss over the last decade, yet the degree to which albedo decline drove this mass loss remains uncertain. We use daily summer glacier surface albedo averaged by decade (2000 − 2009 and 2010 − 2019) derived from Moderate Resolution Imaging Spectroradiometer to investigate how snow and ice darkening influenced glacier mass loss for 25 of the largest and most heavily glaciated regions in North America. Here we show that glacier albedo respectively decreased by 0.019 ± 0.019 and 0.018 ± 0.009 in western North America and in the Canadian Arctic. This decrease in albedo coincides with increased geodetically derived glacier mass loss within these regions (R2 = 0.76, R2 = 0.63; p < 0.01). Modelled surface energy balance and melt rates, forced by European Centre for Medium-Range Weather Forecasts Reanalysis 5th Generation Land reanalysis and regional decadal averages of albedo, indicate that 31% of increased melt rate in Western North America and 41% of increased melt rate in the Canadian Arctic can be attributed to albedo decline. Projected increases in air temperature this century will further reduce glacier albedo, and the resulting positive feedback will further accelerate glacier mass loss.